Genetic diversity in natural watermelon (Citrullus lanatus) populations of Rajasthan - BHAKAR, JITENDRA KUMAR; SHARMA, R; SINGH, PRAVEEN K; SINGH, G (The Indian Journal of Agricultural Sciences, 2017)
The present investigation was carried out to estimate the genetic diversity at molecular level using RAPD primers across 23 genotypes of watermelon [ Citrullus lanatus (Thunb.) Mastum and Nakai]. RAPD analysis was conducted using 14 random primers of which eight primers produced 41 bands, 39 being polymorphic, generating 95% polymorphism. Jaccard similarity index based on RAPD revealed 49.6% average similarity with a range of 28% to 86%. The SAHN clustering based on UPGMA algorithms has put genotypes in two groups, one with 5 genotypes and another with 9 genotypes. The 9 genotype were left separately these being most diverse. High within and between group diversity resulted in poor grouping. Moreover clustering did not show any regional pattern. However, some population specific bands suggested regional influence on diversity.